Knowledge, attitude and practices of pre-exposure prophylaxis (PrEP) on human immunodefficiency virus (HIV) infection of students at National University-Manila - Alcantara, Jerico Ralph N.; Callos, Hannah Mae Z.; Esponilla, Menneth Catherine M.; Mondido, Kristel Anne B.; Salcedo, Chrishelle Amor (Manila : National University, 2023)
This study revealed that there is also a significant relationship between the knowledge and the socio-demographic profile of the respondents.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.